The Oenococcus oeni clpX Homologue Is a Heat Shock Gene Preferentially Expressed in Exponential Growth Phase - Jobin, Michel-Philippe (American Society for Microbiology, 1999)
Using degenerated primers from conserved regions of previously studied clpX gene products, we cloned the clpX gene of the malolactic bacterium Oenococcus oeni. The clpX gene was sequenced, and the deduced protein of 413 amino acids (predicted molecular mass of 45,650 Da) was highly similar to previously analyzed clpX gene products from other organisms. An open reading frame located upstream of the clpX gene was identified as the tig gene by similarity of its predicted product to other bacterial trigger factors. ClpX was purified by using a maltose binding protein fusion system and was shown to possess an ATPase activity. Northern analyses indicated the presence of two independent 1.6-kb monocistronic clpX and tig mRNAs and also showed an increase in clpX mRNA amount after a temperature shift from 30 to 42°C. The clpX transcript is abundant in the early exponential growth phase and progressively declines to undetectable levels in the stationary phase. Thus, unlike hsp18, the gene encoding one of the major small heat shock proteins of Oenococcus oeni, clpX expression is related to the exponential growth phase and requires de novo protein synthesis. Primer extension analysis identified the 5′ end of clpX mRNA which is located 408 nucleotides upstream of a putative AUA start codon. The putative transcription start site allowed identification of a predicted promoter sequence with a high similarity to the consensus sequence found in the housekeeping gene promoter of gram-positive bacteria as well as Escherichia coli.